The usage of Natural Lights in Hotels and Resorts in Saudi Arabia - Dr. Shafiaa Saad Alghamdi; Dr. Sondos Mohammed Rawas (Journal of Arts, Literature, Humanities and Social Sciences, 2025)
The use of natural light in hotel and resort design is becoming more common, particularly in countries like Saudi Arabia, which have a lot of sunlight. These days, more and more people are becoming conscious of the importance of sustainable practices, which, along with enhancing tourist experiences, offer unique design options presented by the local climate and geography. This abstract demonstrates the benefits and drawbacks of incorporating natural light into the Saudi Arabian hospitality industry. Two major advantages to hotels and resorts are that they use natural light sustainability and energy efficiency. Since the days in Saudi Arabia are long and bright, one option to reduce energy consumption is to utilize natural light instead of artificial lighting. Reduced energy use and carbon emissions are two ways these companies are contributing to global and national sustainability goals. Some daylighting options that may boost natural light and lessen the need for artificial lighting throughout the day include skylights, large windows, and light wells. The quantity of natural light that penetrates a room greatly influences how guests feel throughout their time together. According to a study, natural light has several benefits, such as improving mood, increasing productivity, and regulating sleep duration. Saudi Arabian hotels and resorts catering to vacationers and business travellers can find that offering these benefits makes customers more satisfied and loyal. A great instance involves how natural light can improve the mood of a room or common area, making it more welcoming and delightful. To make the most of natural light, Saudi Arabian hotels and resorts need precise architectural planning. It is crucial to balance light intake and thermal comfort in this region because of the intense sunlight and high temperatures. Many contemporary sliding innovations, such as low-emissivity (Low-E) glass, notify light while preventing heat escaping. To further minimize the chances of glare and overheating, shade structures such as pergolas and openings can control the amount of sunlight entering the building. By strategically using natural light, architects and interior designers of hotels and resorts in Saudi Arabia can include artistic and cultural themes. Gardens and mashrabiya screens have used considerable natural light throughout history, two essential components of Arabian architecture.